Influence of the geotectonic activity on volumes of gas seeps in the north part of the Black Sea - Melnichenko, T. A.; Vorobiev, A. I.; Geykman, A. M. (Reports of the National Academy of Sciences of Ukraine, 2016)
The results of the analysis of relations between the geodynamic activity and the volume of releasing hydrocarbon gases in the northern part of the Black Sea are presented.